Pakej pembelajaran perakaunan (penyata pendapatan) / Yaw Chooi Fun - Yaw, Chooi Fun (2001)
This project report is to provide an overview and technical report of what I did in my thesis. The main objective of this project is to develop an Easy Account package including a counting learning package, administration system and automatic accounting system which is suitable for secondary school especially for the SPM account students and teachers. Nowadays, it is essential for the students and teachers to have a computerized system to assist them in the learning and teaching work. The system will enhance the quality of work and reduce the paper use in whole of the processes. Easy Account system includes the following three major parts: Accounting Learning Section, Automatic Accounting System and System Administrator Section. In addition, this system is developed using Visual Basic as a powerful tool for developing tool. EasyAccount system is a Windows-based program that allows the students and teachers to computerized the whole accounting system. The relational behind its development is to meet the rapidly increasing demand for information retrieval, which makes possible the accounting system more efficiently and effectiveness. The prototyping approach was selected for the developing process because the methodology was applied throughput the develop phases of system analysis, design, coding and testing. Visual Basic as Object Oriented Programming Language (OOPL) was selected as main developing tool. Understanding and use the correct software and tools were essential to develop a good working system. Maintenance system is needed for administrator to select Exercises and Pass Year Question frequently for students. Finally, it can be concluded for students that a success student or teacher is always supported by the computer-based system. Hence, Easy Account system is an excellent tool for them.